Historic capital : preservation, race, and real estate in Washington, D.C. - Logan, Cameron, 1974- (University of Minnesota Press, 2017)
"For much of the postwar era, Washingtonians battled to make the city their own, fighting the federal government over the basic question of home rule, the right of the citys residents to govern their local affairs. Urban historian Cameron Logan examines how the historic preservation movement played an integral role in Washingtonians claiming the city as their own. Going back to the earliest days of the local historic preservation movement in the 1920s, Logan shows how Washington, D.C.s historic buildings and neighborhoods have been a site of contestation between local interests and the expansion of the federal governments footprint. He carefully analyzes the long history of fights over the right to name and define historic districts in Georgetown, Dupont Circle, and Capitol Hill and documents a series of high-profile conflicts surrounding the fate of Lafayette Square, Rhodes Tavern, and Capitol Park, SW before discussing D.C. today. Diving deep into the racial fault lines of D.C., Historic Capital also explores how the historic preservation movement affected poor and African American residents in Anacostia and the U Street and Shaw neighborhoods and changed the social and cultural fabric of the nations capital. Broadening his inquiry to the United States as a whole, Logan ultimately makes the provocative and compelling case that historic preservation has had as great an impact on the physical fabric of U.S. cities as any other private or public sector initiative in the twentieth century."--Provided by publisher